2022
DOI: 10.24843/jkb.2022.v12.i01.p14
|View full text |Cite
|
Sign up to set email alerts
|

Leading Sectors that Drive the Economy of Bali during the COVID-19 Pandemic

Abstract: Due to the COVID-19 pandemic, the economy of Indonesia has weakened and contracted, although currently, the economy has recovered from it. The economy of Bali has experienced its lowest growth of all time. This is due to the huge impact of the COVID-19 pandemic on tourism in Bali, which is its economic locomotive. This research aims to analyze the potential sectors that can be developed by each regency and city in Bali to boost its economic recovery. The research used the LQ and overlay methods. The results of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…Hence, the discourse for decades of the synergy of tourism and agriculture in Bali may be realized. To be precise, the development of the tourism sector which has been proven capable of providing prosperity for the people of Bali for the previous decades must remain the locomotive of development by not neglecting the agricultural, fisheries, and livestock sectors (Setyari, Widanta, Sarjana, & Gupta, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Hence, the discourse for decades of the synergy of tourism and agriculture in Bali may be realized. To be precise, the development of the tourism sector which has been proven capable of providing prosperity for the people of Bali for the previous decades must remain the locomotive of development by not neglecting the agricultural, fisheries, and livestock sectors (Setyari, Widanta, Sarjana, & Gupta, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…But unexpectedly, the pandemic hit in 2019 which is causing the grand narrative of tourism in Bali which is the foundation of life for most people in Bali is facing a very serious challenge. It is also reported that Bali is one of the regions in Indonesia that was hit hardest by the economic impact of the Covid-19 pandemic (Setyari et al, 2022).…”
Section: The Challenge Of the Grand Narrative Of Tourism In Balimentioning
confidence: 99%
“…Desa Bongancina yang terletak di Kecamatan Busungbiu, Kabupaten Buleleng memiliki karakteristik alam yaitu perbukitan kopi yang dikelilingi sungai tadah hujan yang dimanfaatkan sebagai subak (sistem pengairan di Bali). Masyarakat dominan berprofesi sebagai petani kopi, namun ada beberapa warga yang beralih menjadi petani buah dan sayur sebagai upaya ketahanan pangan di masa pandemi Covid-19 yang tidak menentu (Setyari et al, 2022). Desa perbukitan kopi ini belum dinyatakan sebagai desa wisata.…”
Section: Selayang Pandang Desa Bongancinaunclassified